Beschäftigung, Armut und die Millenniumsziele der Vereinten Nationen - Prediger, Sebastian; Lay, Jann; Giesbert, Lena; Ostermeier, Martin (2012)

Co-managing common-pool resources: Do formal rules have to be adapted to traditional ecological norms? - Prediger, Sebastian; Vollan, Björn; Frölich, Markus (Ecological Economics, 2013)

Decent work in a post-2015 development agenda - Prediger, Sebastian; Lay, Jann (2013)

Economic behaviour and context: Five experimental studies on the impact of ecological and institutional context factors in southern African commons - Prediger, Sebastian (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2012)

Microcredit and Business-Training Programs: Effective Strategies for Micro- and Small Enterprise Growth? - Prediger, Sebastian; Gut, Gundula (2014)

Potentials and limitations of communal conservancies in southern Namibia - Prediger, Sebastian; Kirk, Michael (Biodiversity in Southern Africa. Volume 3: Implications for Landuse and Management, 2010)

Resource Scarcity and Antisocial Behavior - Prediger, Sebastian; Vollan, Björn; Herrmann, Benedikt (Journal of Public Economics, 2014)
This paper examines whether exposure to persistent resource scarcity on the commons affects pastoralists' readiness to engage in antisocial behavior towards their fellow commons users. The region under study is divided into two areas according to exogenous variations in biomass production stemming from geological peculiarities. We conducted a joy-of-destruction game with pastoralists from both areas and provide evidence for a positive relationship between antisocial behavior and long-term exposure to scarcity. Antisocial behavior among villagers occurs twice as often in an area where resources are scarcer and competitive pressure is higher. Our results remain robust to the inclusion of various controls, including beliefs, socio-demographics, absolute and relative income, and within-group inequality. If one interprets decreasing another participant's payoff below one's own as a tendency towards conflict behavior, our results suggest a higher risk of conflict among resource users in areas of greater scarcity.

SMARTer indicators for decent work in a post-2015 development agenda: Discussion and a proposal - Prediger, Sebastian; Linde, Sarah; Lay, Jann; Ostermeier, Martin (International Labour Review, 2015)

The impact of culture and ecology on cooperation in a common-pool resource experiment - Prediger, Sebastian; Vollan, Björn; Frölich, Markus (Ecological Economics, 2011)

The influence of collective property rights on grazing management in a semi-arid region - Prediger, Sebastian; Frölich, Markus; Vollan, Björn (African Journal of Agricultural Research, 2010)

Understanding norms and propensities for cooperation and collective action: economic experiments within BIOTA - Prediger, Sebastian; Pröpper, Michael (Biodiversity in Southern Africa. Volume 2: Patterns and Processes at Regional Scale, 2010)